Sistem Pemantauan Ketebalan Debu & Suhu Pada Ruangan Menggunakan Aplikasi Telegram berbasis IoT - Agum Prima Pratama; Fahri Syeha Maulana; Rini Suwartika Kusumadiarti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
By following the technological advamces in this world, most people want to do everything easily, practically. without interfering with the work they are doing during the current pandemic, technology is also urgently needed by large companies where many of the workers are at home (Work From Home), so the place for the big company is just a big empty and abandoned building. To anticipate abandoned buildings, it is necessary to do cross checks periodically so that the buildings are kept clean and to make it easier for us to do cross checks, using Internet Of Things (IoT) technology. By observing and analyzing it, a Dust and Temperature Monitoring System was created. created using Telegram. That's where this tool is directed so that we can continue to monitor the situation of the building remotely in real time.